Lifting the profile of deep soil carbon in New Zealand’s managed planted forests - Loretta G. Garrett; Katherine A. Heckman; Angela R. Possinger; Brian D. Strahm; Jeff A. Hatten; Fiona P. Fields; Steve A. Wakelin (Carbon Balance and Management)
Abstract Background Forest soils are a globally significant carbon-store, including in deep layers (> 30 cm depth). However, there is high uncertainty regarding the response of deep soil organic carbon (DSOC) to climate change and the resulting impact on the total OC budget for forest ecosystems. Managed forests have an opportunity to reduce the risk of DSOC loss with climate change, however, the basic understanding of DSOC is lacking. Planted forests in New Zealand are managed with very limited knowledge of DSOC, both in the amount and the capacity of the soil to continue to store carbon with climate change. In this study, we explore DSOC stocks to at least 2 m depth at 15 planted forest sties in New Zealand. We also explore DSOC radiocarbon age and soil mineralogy, then contextualise our results within international SOC datasets and climate change vulnerability frameworks to identify research priorities for New Zealand’s planted forest soils. Results DSOC stocks and soil mineralogy in New Zealand’s planted forests were diverse both horizontally across soil types and vertically throughout the soil profile. Critically, limiting measurements of SOC to the top 30 cm misses more than half of the SOC stocks present to at least 2 m depth (mean 57%; range 33–72%). At depth, mineral-associated OC was the dominant fraction of DSOC (average > 90%) and was on average much older (> 1000 years) than the current planted forest land use (< 100 years). Conclusions This small case study highlights that New Zealand’s planted forests contain substantial stocks of DSOC, much of which is older than the current forest land use. The deep soils were dominated by reactive metals, and although the age of DSOC suggest long-term stability, the large contribution of reactive metal-mediated SOC stabilisation may indicate vulnerability to warming soil temperatures relative to other climate change factors. There is a pressing need to expand soil sampling to greater depths and establish a robust SOC baseline for New Zealand’s planted forests. This is essential for enabling spatial predictions of DSOC dynamics under future climate scenarios, identify the key controls on DSOC persistence, and concomitant impacts on forest ecosystem function and resilience.